In vitro biocompatibility and electrical stability of thick-film platinum/gold alloy electrodes printed on alumina - Carnicer-Lombarte, Alejandro; Lancashire, Henry T; Vanhoestenberghe, Anne (Journal of neural engineering, 2017)
Objective. High-density electrode arrays are a powerful tool in both clinical neuroscience and basic research. However, current manufacturing techniques require the use of specialised techniques and equipment, which are available to few labs. We have developed a high-density electrode array with customisable design, manufactured using simple printing techniques and with commercially available materials. Approach. Electrode arrays were manufactured by thick-film printing a platinum-gold alloy (Pt/Au) and an insulating dielectric on 96% alumina ceramic plates. Arrays were conditioned in serum and serum-free conditions, with and without 1 kHz, 200 µA, charge balanced stimulation for up to 21 d. Array biocompatibility was assessed using an extract assay and a PC-12 cell contact assay. Electrode impedance, charge storage capacity and charge injection capacity were before and after array conditioning. Main results. The manufactured Pt/Au electrodes have a highly porous surface and exhibit electrical properties comparable to arrays manufactured using alternative techniques. Materials used in array manufacture were found to be non-toxic to L929 fibroblasts by extract assay, and neuronal-like PC-12 cells adhered and extended neurites on the array surfaces. Arrays remained functional after long-term delivery of electrical pulses while exposed to protein-rich environments. Charge storage capacities and charge injection capacities increased following stimulation accounted for by an increase in surface index (real surface area) observed by vertical scanning interferometry. Further, we observed accumulation of proteins at the electrode sites following conditioning in the presence of serum. Significance. This study demonstrates the in vitro biocompatibility of commercially available thick-film printing materials. The printing technique is both simple and versatile, with layouts readily modified to produce customized electrode arrays. Thick-film electrode arrays are an attractive tool that may be implemented for general tissue engineering and neuroscience research.